Safety assessment of an existing bridge deck subject to different damage scenarios through the global safety format ECOV - Bertagnoli, Gabriele; Ferrara, Mario; Miceli, Elena; Castaldo, Paolo; Giordano, Luca (Engineering structures, 2024)
The assessment of existing reinforced concrete structures, especially bridges and viaducts, nowadays is one of the most relevant aspects for engineers. In fact, due to the old age of a large part of the infrastructure assets and the deteriorating conditions affecting the structural elements, their safety with respect to the ultimate limit states may be compromised. In this perspective, the assessment by means of global safety formats employing non-linear finite element analyses can be an extremely useful tool. In this context, the study proposes to relate the safety level to the damage through 3D global non-linear numerical analyses. Specifically, the assessment of an existing prestressed reinforced concrete bridge deck is carried out by means of the global safety format denoted as “Estimation of Coefficient of Variation” (ECOV) assuming different damage scenarios. In fact, the safety of the structure is initially assessed with respect to the ultimate limit state in its undamaged condition. Subsequently, different damage scenarios, derived from the inspections, are numerically studied. For each damage scenario, the safety of the deck is evaluated with respect to the ultimate limit state relating the safety loss to the damage level. Finally, damage thresholds for this type of structure are defined on specific static parameters. •Safety of an existing prestressed reinforced concrete bridge deck is assessed.•3D NLFE models are defined within the global safety format ECOV.•A visco-elastic analysis is performed to reproduce the time-dependent effects.•Different damage scenarios are simulated by varying degradation characteristics.•Specific damage thresholds are numerically proposed and related to damage level.